Nanodrugs Manipulating Endoplasmic Reticulum Stress for Highly Effective Antitumor Therapy - Xiang, Yuting; Liu, Min; Yang, Yunrong; Wang, Yubo; Qiu, Yige; Tu, Shiqi; Jiang, Yitian; Nan, Yayun; Zhang, Xiaojie; Huang, Qiong (Frontiers in Pharmacology, 2022)
Cancer is one of the leading causes of death worldwide due to high morbidity and mortality. Many attempts and efforts have been devoted to fight with cancer. Owing to the significant role of endoplasmic reticulum (ER) in cell function, inducing ER stress can be promising for cancer treatment. However, the sustained activation of cytoprotective unfolded protein response (UPR) present a tremendous obstacle for drugs to inducing unsolved ER stress in tumor cells, especially small-molecule drugs with poor bioavailability. Therefore, many emerging nanodrugs inducing and amplifying ER stress have been developed for efficient cancer treatment. More importantly, the novel discovery of ER tress in immunogenic cell death (ICD) makes it possible to repurpose anti-tumor drugs for immunotherapy through nanodrug-based strategies to amplify ER stress. Therefore, this minireview is aim to provide a comprehensive summary of the latest developments of the strategies underlying nanodrugs in the treatment of cancer via manipulating ER stress. Meanwhile, the prospects of ER stress-inducing nanodrugs for cancer treatment are systematically discussed, which provides a sound platform for novel therapeutic insights and inspiration for design of nanodrugs to treat cancer.